A novel HLA‐DQB1*04 variant, HLA‐DQB1*04:90, identified in a Chinese Han individual. (7th October 2022) - Quan, Zhan‐Rou; Zou, Hong‐Yan; Zhou, Dan
Abstract : Identification of the novel HLA‐DQB1*04:90 allele that differs from DQB1*04:01:01:01 at nucleotide 183 in exon 2 from A to T.